Teaching by Inquiry: Integrating Socratic, Maieutic, and Indirect Communication in EMI - Tooley, Melynie (12th International Scholars Conference 2025, 2026)
The rise of English as a Medium of Instruction (EMI) presents complex challenges for educators tasked with teaching subject content in English to linguistically diverse students. While EMI often prioritizes content delivery, it frequently neglects the cognitive and communicative demands of learning in a second language. This paper explores how three inquiry-based pedagogical approaches—Indirect Communication, the Maieutic Method, and the Socratic Method—can support deeper engagement in EMI contexts. Rooted in purposeful questioning and dialogic interaction, these traditions foster interpretive thinking, learner agency, and reflective language use. Each method is examined for its philosophical grounding and practical application, with attention to how they can enhance both content understanding and English proficiency. By shifting the teacher’s role from content expert to facilitator of inquiry, this framework offers a more inclusive, student-centered model for EMI. The paper concludes with a practical sequence for implementation that integrates language, thinking, and disciplinary learning through layered questioning strategies.